Impact response of ductile self-reinforced composite corrugated sandwich beams. (15th August 2016) - Schneider, C.; Kazemahvazi, S.; Russell, B.P.; Zenkert, D.; Deshpande, V.S.
Abstract: Corrugated sandwich beams made entirely from self-reinforced poly (ethylene terephthalate) SrPET are manufactured and tested dynamically. The beams are subjected to impact loading at the mid-span using a metal foam projectile and the beam deflection is measured. For sandwich beams with a constant areal mass, beams with a high mass portion in the core webs outperform configurations with a high mass portion in the face sheets (given that the face sheets are thick enough to carry the transversal loads induced by the core webs). Reinforcing the face sheet – core web interface further improves the impact response. The strain rate sensitivity of SrPET has also been investigated. A three-dimensional finite element (FE) model has been developed to simulate the impact event and a good agreement is found with the measured response. It is found that corrugated sandwich beams made from SrPET has competitive impact performance compared to similar sandwich beams with equal mass and geometry out of aerospace grade aluminium and carbon fiber/high performance foam sandwich.